Nipple hyperkeratosis in a 15-year-old girl. - Maheshwari, R.; Phiske, M.; Someshwar, S. (European Journal of Pediatric Dermatology, 2025)
Hyperkeratosis of the nipple and areola (HNA) is a benign condition characterized by warty thickening and pigmentation of the nipple, areola, or both. This disorder is rare, about 150 cases have been reported till september 2022. Nevertheless, the prevalence of this condition is likely underestimated because the skin lesions are usually asymptomatic and subsequently, there may not be sufficient motivation for affected persons to seek medical care. Pathophysiology of HNA is unclear. It is either unilateral or bilateral, strictly limited to the nipple and areola. Clinically, it is characterized by hyperpigmented, hyperkeratotic verrucous plaques, without induration, erythema or discharge. Diagnosis is clinical, aided by dermoscopy and histopathology. Several therapeutic options, both medical and surgical have been tried for cosmetic improvement with variable success. A 15-year-old female child, presented for evaluation of hyperpigmented to flesh coloured plaque with finger like projections over the surface, involving the both nipples since 2 years. She had prior crusting over nipples, with subsequent shedding. She had applied lanolin ointment for 1 year, without improvement. There was no history of prior pre-existing dermatosis, similar lesions in the past or family. The dermoscopy revealed papillated growth, white clods, linear vessels, brownish crust on surface and peripheral brown pigmentation which allowed clinic-dermoscopic diagnosis of HNA. She was initially treated with topical retinoids with subsequent addition of cryotherapy with significant clinico-dermoscopic improvement at end of three months. HNA, though rare, has to be kept as a differential diagnosis for lesions restricted to nipples. Dermoscopy can prove to be a diagnostic as well as prognostic tool for nipple hyperkeratosis.